Fit for School: The Samurai School Program - Wernicke, Thomas (Med Acupunct, 2016)
For the past several years, an increasing number of schools across Europe have been using the Samurai School Program successfully. In 2015, it was also introduced in the United States with great acceptance. The program is aimed at treatment of children on the autistic spectrum, including those with attention-deficit hyperactivity disorder or similar disorders. Given that such children lack social skills and may be prone to violence, treating this disorder is of concern. The objective of the Samurai School Program is to address social and violent tendencies in youth.